Histone Deacetylase Sirtuin 1 Promotes Loss of Primary Cilia in Cholangiocarcinoma. Issue 6 (27th September 2021) - Pant, Kishor; Peixoto, Estanislao; Richard, Seth; Biswas, Aalekhya; O'Sullivan, M. Gerard; Giama, Nasra; Ha, Yeonjung; Yin, Jun; Carotenuto, Pietro; Salati, Massimiliano; Ren, Yanan; Yang, Rendong; et al.
Abstract : Background and Aims: Sirtuin 1 (SIRT1) is a complex NAD + ‐dependent protein deacetylase known to act as a tumor promoter or suppressor in different cancers. Here, we describe a mechanism of SIRT1‐induced destabilization of primary cilia in cholangiocarcinoma (CCA). Approach and Results: A significant overexpression of SIRT1 was detected in human CCA specimens and CCA cells including HuCCT1, KMCH, and WITT1 as compared with normal cholangiocytes (H69 and NHC). Small interfering RNA (siRNA)‐mediated knockdown of SIRT1 in HuCCT1 cells induced cilia formation, whereas overexpression of SIRT1 in normal cholangiocytes suppressed ciliary expression. Activity of SIRT1 was regulated by presence of NAD+ in CCA cells. Inhibition of NAD ‐producing enzyme nicotinamide phosphoribosyl transferase increased ciliary length and frequency in CCA cells and in SIRT1‐overexpressed H69 cells. Furthermore, we also noted that SIRT1 induces the proteasomal mediated degradation of ciliary proteins, including α‐tubulin, ARL13B, and KIF3A. Moreover, overexpression of SIRT1 in H69 and NHC cells significantly induced cell proliferation and, conversely, SIRT1 inhibition in HuCCT1 and KMCH cells using siRNA or sirtinol reduced cell proliferation. In an orthotopic transplantation rat CCA model, the SIRT1 inhibitor sirtinol reduced tumor size and tumorigenic proteins (glioma‐associated oncogene 1, phosphorylated extracellular signal‐regulated kinase, and IL‐6) expression. Conclusions: In conclusion, these results reveal the tumorigenic role of SIRT1 through modulation of primary cilia formation and provide the rationale for developing therapeutic approaches for CCA using SIRT1 as a target.